COVID-19 AND COAGULATION DYSFUNCTION: A SYSTEMATIC REVIEW - Talilah, Stephanie (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
The mechanism of blood coagulation, which is responsible for maintaining hemostasis, is an intricate process that is carried out by a number of clotting factors. The components I, II, IX, X, XI, and XII are the ones that make up the intrinsic route. The initial processes that set off this cycle of inflammation and thrombosis take place in the alveoli of the lungs. It is in these alveoli that the SARS-CoV-2 virus penetrates the alveolar epithelium through the angiotensin converting enzyme (ACE)-2 receptor. This leads to a significant inflammatory response, which, through a variety of mechanisms, commences the thrombotic stage of the process. Patients who are younger and do not have any other medical conditions can suffer from a serious disease if there is an excessive release of cytokines. Researchers have shown a link between having elevated serum levels of several inflammatory cytokines and chemokines and having a severe disease or even death. Numerous investigations have unequivocally established that there is a causal connection between inflammation and thrombosis, as well as a two-way exchange of information between the two. An increase in high levels of C-reactive protein (CRP), lactate dehydrogenase (LDH), ferritin, interleukin-6, and D-dimer are proof that COVID-19 creates a hyper pro-inflammatory condition. This is shown by the fact that these levels increase. Patients diagnosed with COVID-19 were shown to have a correlation that went in both directions between the levels of IL-6 and fibrinogen, which lends credence to the concept of inflammatory thrombosis.